KARAKTERISTIK BROWNIES PANGGANG DENGAN SUBSTITUSI TEPUNG KULIT ARI KOPI (Coffea sp) - Zainur Romadan; Nita Yessirita; Leffy Hermalena; Inawaty Sidabalok (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
The purpose of this study was to determine the characteristics of the best roasted brownies with the substitution of coffee husk flour in making baked brownies that were preferred by the panelists. This study used a completely randomized design (CRD) with 5 treatment levels and 3 replications. Observational data were analyzed using ANOVA and Duncan's New Multiple Range Test (DNMRT) advanced test at a level of 1%. The treatment in this study was the substitution of wheat flour with coffee husk flour (A=70:30, B=60:40, C=50:50, D=40:60, E=30:70). The results of this study indicate that the substitution of wheat flour with coffee husk flour has an effect on the water content, ash, fat, protein, and total sugar content. Based on the organoleptic test, the baked brownies with treatment C (wheat flour ratio: coffee husk flour = 50: 50) were the most preferred by the panelists and met the quality requirements of SNI 01-3840-1995 with a composition of water content (10.03%), ash content (0.95%), fat content (7.22%), protein content (15.23%), and total sugar content (32.71%).